A Discrete Analogue of Energy Integral for a Difference Scheme for Quasilinear Hyperbolic Systems - R. D. Aloev; Z. K. Eshkuvatov; M. U. Khudayberganov; N. M. A. Nik Long (Scientific Research Publishing company, 2024)
Volume :9 No:7